A Discourse of Marriage Principles in a Multicultural Society in Indonesia: Mono and Polygamous Practices - Lestari, Endriyani; El Rahman, Abdul Malik Hasyim; Zuhud, Abdul Kareem (Contemporary Issues on Interfaith Law and Society, 2024)
This paper delves into the discourse surrounding marriage principles within Indonesia's diverse multicultural landscape, with a particular focus on both monogamous and polygamous practices. As a nation characterized by rich cultural and religious diversity, Indonesia provides a unique context for examining the dynamics of marital norms and traditions. Through a comprehensive analysis, this study explores the historical, legal, and socio-cultural dimensions of monogamous and polygamous marriages, shedding light on their prevalence, legal frameworks, and societal implications. Drawing upon legal perspectives, societal attitudes, and empirical evidence, this discourse aims to provide a nuanced understanding of the complexities inherent in marital practices within Indonesia's multicultural society. Ultimately, this study contributes to broader discussions on marriage, diversity, and legal pluralism, offering insights into the evolving nature of marital norms and their intersection with Indonesia's multicultural fabric.